Self-Care and Family Support Improves the Quality of Life of Coronary Heart Disease Patients - Emil Huriani; Rifdatul Jannah; Dally Rahman (NERS Jurnal Keperawatan, 2026)
Coronary heart disease (CHD) can reduce the patient's quality of life. An important aspect in influencing the quality of life for CHD patients is self-care and family support for CHD patients, but this is often overlooked. This study aimed to determine the relationship between self-care and family support and the quality of life of patients with CHD at the Cardiac Clinic of RSUP Dr. M. Djamil Padang. A cross-sectional approach was used in this study. Totaly 303 participants were recruited in this study using purposive sampling technique. Instrument used were the MacNew Heart Disease Health-related Quality of Life Questionnaire, Self-Care of Coronary Heart Disease Inventory and family support questionnaires. The data analysis used was the Spearman rank test. The results showed that mean score of self-care was 64.95 (SD± 5.993), mean score of family support was 38.73 (SD± 2.827) and mean score of quality of life of was 143.96 (SD± 11.25). There was a relationship between self-care and quality of life (r=0.500; p= 0.001) and there was a relationship between family support and the quality of life of CHD patients (r=0.416; p=0.001). Self-care and family support were positively related to quality of life at moderate level. Patients need to improve their ability to perform self-care while family members need to provide supports to patients in order to increase patients’ quality of life. Health education about self-care needs to be provided to patients and their families to improve self-care skills and the quality of life of patients with coronary heart disease.